2012
DOI: 10.3171/2012.2.focus1214
|View full text |Cite
|
Sign up to set email alerts
|

Absence of abnormal vessels in the subarachnoid space on conventional magnetic resonance imaging in patients with spinal dural arteriovenous fistulas

Abstract: Spinal dural arteriovenous fistula (DAVF) is an uncommon condition that can be difficult to diagnose. This often results in misdiagnosis and treatment delay. Although conventional MRI plays an important role in the initial screening for the disease, the typical MRI findings may be absent. In this article, the authors present a series of 4 cases involving patients with angiographically proven spinal DAVFs who demonstrated cord T2 prolongation on conventional MRI but without abnormal subarachnoid flow vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The key radiological difference between SDAVF and LETM in NMOSD when present are the abnormal dilated intradural veins of the spinal cord on T2-weighted MRI (flow void) and/or serpentine enhancing vascular structures on T1-weighted contrast-enhanced MRI, mostly in the dorsal surface of the spinal cord. However, these findings in conventional MRI may not be observed or easily differentiated from the normal vascular structures of the spinal cord, especially in the early stage of disease 154,155 (Figure 8). Though some advocate the use of spinal MR angiography in the diagnosis of SDAVF, 155 catheter angiography remains a diagnostic procedure of choice (Figure 8).…”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%
See 1 more Smart Citation
“…The key radiological difference between SDAVF and LETM in NMOSD when present are the abnormal dilated intradural veins of the spinal cord on T2-weighted MRI (flow void) and/or serpentine enhancing vascular structures on T1-weighted contrast-enhanced MRI, mostly in the dorsal surface of the spinal cord. However, these findings in conventional MRI may not be observed or easily differentiated from the normal vascular structures of the spinal cord, especially in the early stage of disease 154,155 (Figure 8). Though some advocate the use of spinal MR angiography in the diagnosis of SDAVF, 155 catheter angiography remains a diagnostic procedure of choice (Figure 8).…”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%
“…However, these findings in conventional MRI may not be observed or easily differentiated from the normal vascular structures of the spinal cord, especially in the early stage of disease 154,155 (Figure 8). Though some advocate the use of spinal MR angiography in the diagnosis of SDAVF, 155 catheter angiography remains a diagnostic procedure of choice (Figure 8). SDAVF can be treated by either endovascular embolization or surgical ligation of the fistula.…”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%
“…However, if the shunt volume is small, no abnormal vessels may be observed on conventional sequences. 1 , 12 In our 3T MRI study, we observed flow voids on 13% of T 1 WI- and on 69–81% of T 2 WI scans. Krings and Geibprasert 1 suggested that for the identification of abnormal vessels of SDAVF, heavily T 2 -weighted sequences were more useful than standard T 2 WI scans.…”
Section: Discussionmentioning
confidence: 54%
“…5,6 However, in cases where the shunt volume is small or mainly drained into the ventral medullary vein, there may not be a recognizable dilated vein on MRI, so-called MRI-occult arteriovenous fistula. 79 Lasjaunias et al. have reported the anatomical explanation of this MRI-occult arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 95%